Raw Materials treated with Nanotechnology and its Use in Contemporary Sculpture - Mohamed Mohamed Ali Shaheen; Amna Haroon Mohamed Al Targee; Marwan Abdu-Allah Hussien (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2021)
It’s hard to imagine just how small nanotechnology is. One nanometer is a billionth of a meter,  Nano science and nanotechnology involve the ability to see and to control individual atoms and molecules. Everything on Earth is made up of atoms—the food we eat, the clothes we wear, the buildings and houses we live in, and our own bodies, but something as small as an atom is impossible to see with the naked eye. In fact, it’s impossible to see with the microscopes typically used in a high school science classes. The microscopes needed to see things at the nanoscale were invented in the early 1980s., and once scientists had the right tools, such as the scanning tunneling microscope (STM) and the atomic force microscope (AFM), the age of nanotechnology was born. Although modern nano science and nanotechnology are quite new, nano scale materials were used for centuries, but The artists back then just didn’t know that the process they used to create these beautiful works of art actually led to changes in the composition of the materials they were working with. Today's scientists and engineers are finding a wide variety of ways to deliberately make materials at the nano scale to take advantage of their enhanced properties such as higher strength, lighter weight, increased control of light spectrum, and greater chemical reactivity than their larger-scale counterparts. Lately , Some sculptures are built on a grandiose scale, impressing the observer with their sheer size. These are not those sculptures. These  feats of technical skill and nanotechnology pack incredibly detailed features into forms no bigger than the eye of a needle and in some cases, even smaller.